2022
DOI: 10.1155/2022/6721958
|View full text |Cite
|
Sign up to set email alerts
|

Fibropreventive and Antifibrotic Effects of Uncaria gambir on Rats with Pulmonary Fibrosis

Abstract: Pulmonary fibrosis causes scar tissue formation that disrupts the functioning of the lungs. Uncaria gambir (Hunter) Roxb (hereafter gambir)—a plant native to West Sumatra in Indonesia—contains flavonoid (+)-catechin, which has strong antioxidant activity and can be used to combat pulmonary fibrosis. This random in vivo experimental study analyzed the antifibrotic effect of gambir on the lungs of rats with bleomycin-induced fibrosis. The subjects were 10 groups of 10-week-old male rats weighing around 200–250 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…There are an estimated 3.2 million cases of IPF globally and 1.22 million new cases each year, according to the World IPF Joint Association. IPF cases in Indonesia reached 6.26-7.73% of the 1 million population in 2017 and are predicted to continue to increase [2]. The long-term effects of COVID-19 virus infection may increase the prevalence of IPF [3].…”
Section: Introduction mentioning
confidence: 99%
“…There are an estimated 3.2 million cases of IPF globally and 1.22 million new cases each year, according to the World IPF Joint Association. IPF cases in Indonesia reached 6.26-7.73% of the 1 million population in 2017 and are predicted to continue to increase [2]. The long-term effects of COVID-19 virus infection may increase the prevalence of IPF [3].…”
Section: Introduction mentioning
confidence: 99%
“…Recent studies proved that the bioactive compounds of gambir have antibacterial, anticancer, anti-inflammation, as well as antifibrotic effects [ 10 , 11 , 12 , 13 ]. Desdiani et al [ 14 , 15 ] found using in vivo study that gambir has antifibrotic effect against lung fibrosis through inhibition of nuclear factor kappa-B (NF-κB) and transforming growth factor receptor (TGF-βR). In line with these findings, Sriningsih [ 16 ] identified that gambir extract could inhibit the expression of tissue inhibitor matrix metalloproteinase (TIMP) and collagen-1 in rat liver fibrosis tissue.…”
Section: Introductionmentioning
confidence: 99%
“…(27) In this connection, pulmonary fibrosis occurs due to the formation of scar tissue that interferes with lung function. (28) It has been demonstrated that inhalation of toxic compounds causes inflammation, (29,30) progressive lung injury, (29) and fibrosis in the rat. (18,29,31) As with COPD, morphometric measurements have been made in lung cystic fibrosis.…”
Section: Introductionmentioning
confidence: 99%